Prediction of histone deacetylase inhibition by triazole compounds based on artificial intelligence - Wang, Yiran; Zhang, Peijian (Frontiers in Pharmacology, 2023)
A quantitative structure-activity relationship (QSAR) study was conducted to predict the anti-colon cancer and HDAC inhibition of triazole-containing compounds. Four descriptors were selected from 579 descriptors which have the most obvious effect on the inhibition of histone deacetylase (HDAC). Four QSAR models were constructed using heuristic algorithm(HM), random forest(RF), radial basis kernel function support vector machine(RBF-SVM) and support vector machine optimized by particle swarm optimization(PSO-SVM). Furthermore, the robustness of four QSAR models were verified by K-fold cross-validation method, which was described by Q 2 . In addition, the R 2 of the four models are greater than 0.8, which indicates that the four descriptors selected are reasonable. Among the four models, model based on PSO-SVM method has the best prediction ability and robustness with R 2 of 0.954 , root mean squared error(RMSE) of 0.019 and Q 2 of 0.916 for the training set and R 2 of 0.965, RMSE of 0.017 and Q 2 of 0.907 for the test set. In this study, four key descriptors were discovered, which will help to screen effective new anti-colon cancer drugs in the future. Key words：colon cancer; HDAC Inhibition; quantitative structure-activity relationship; support vector machine; particle swarm optimizationColon and rectal cancers are the most common gastrointestinal tumors [1,2] .